Serum Concentration of Ropivacaine After Repeated Administration to Several Parts of the Head During Awake Craniotomy: A Prospective Cohort Study - Sato, Takehito; Ando, Takahiro; Asano, Ichiko; Mori, Atsushi; Motomura, Kazuya; Nishiwaki, Kimitoshi (Frontiers in Medicine, 2022)
Introduction: During awake craniotomy, effective use of local anesthetics, such as ropivacaine, is critical. Blood concentrations of ropivacaine after repeated administration over a short period during awake craniotomy have not been studied. Materials and Methods: In this prospective cohort study, we evaluated serum concentrations of ropivacaine 15 min after each administration during awake craniotomy at Nagoya University Hospital between April 5, 2018 and August 31, 2019 to determine the safe dose. A total of 30 patients scheduled to undergo elective awake craniotomy were included. Patients were injected with 0.375% ropivacaine before the awake phase at the following points: scalp block (T1), headpin area (T2), skin incision area (T3), temporal muscle (T4), and dura mater (T5). Arterial blood samples were collected 15 min after ropivacaine administration. In addition to the blood concentrations of ropivacaine, complications during the awake phase were evaluated as secondary endpoints. Results: The mean total dose of ropivacaine was 5.01 ± 0.68 mg/kg (maximum total dose: 6.30 mg/kg). The mean interval from T1 to T5 was 128.0 ± 17.7 min. The maximum serum concentration did not exceed the toxicity threshold of 4.3 μg/mL in any patient (mean serum concentration: T1, 1.23 ± 0.36 μg/mL; T5, 0.82 ± 0.26 μg/mL). No addiction symptoms were observed during awakening in any case. Conclusion: Our results show that, in cases of awake craniotomy with repeated anesthetic administration, a total dose of up to 5.0 mg/kg is safe, without addiction symptoms. Relatively large amounts of ropivacaine can be safely injected during awake craniotomy.